Creative Strategy of Producer of Leyeh-Leyeh Program with Dolan-Dolan Theme RBTV Jogja in Maintaining Regional Cultural Identity - Ulum, Miftakhul; Muhammad Muttaqien (Jogjakarta Communication Conference (JCC), 2024)
The leyeh-leyeh program with the theme dolan-dolan is a locally charged variety show program containing cultural arts, creative economy, tourism, superior products and regional potential as one of the efforts made to shape the image of local TV and at the same time strengthen regional cultural identity. This research aims to analyze the creative strategy applied by the producer of the leyeh-leyeh program with the theme dolan-dolan RBTV Jogja in maintaining regional cultural identity through 13 elements of creative strategy. This research uses qualitative methods with data collection techniques used, namely interviews and documentation. The data analysis technique used is the Miles and Huberman model, data analysis is carried out through data reduction, data presentation and conclusion drawing. The data validity test used is source triangulation. The results of this study conclude that there are elements of creative strategies used by the producer of the leyeh-leyeh RBTV Jogja program in maintaining regional cultural identity. Elements of creative strategy applied by producers are target audience, script language, program format, punching line, gimmick, clip hanger, time and bumper, artistic stylist, music and fashion, logo and music track. The script language, program format, music and fashion are the most distinctive elements. Fashion in RBTV Jogja's leyeh-leyeh dolan-dolan is Javanese traditional clothing and music uses Javanese music while the format of the program used is a variety show coupled with comedy in Javanese. This shows that the leyeh-leyeh program with the theme of dolan-dolan promotes local culture in maintaining regional cultural identity.